CSC444: Java Programming / College of Computing, Informatics and Mathematics - UiTM, College of Computing, Informatics and Mathematics (2023)
The course is designed to introduce students to intermediate level Java programming language and produce students who are able to solve extensive computer-based and web-based problems. It emphasizes various aspects of problem solving and develops application using GUI, Applet and web component technology.